PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA POSTER TERHADAP PENGETAHUAN MANAJEMEN HIPERTENSI PADA PRA LANSIA DAN LANSIA WANITA USIA 55-64 TAHUN DI WILAYAH KERJA PUSKESMAS RAWANG KOTA SUNGAI PENUH - Rahmita Yanti; Harleni Harleni; Laudia Novela Regita (Ensiklopedia of Journal, 2022)
Hypertension can increase the risk of cardiovascular disease. Every 20 mmHg increase in systolic blood pressure or 10 mmHg diastolic blood pressure. Based on data obtained from the Rawang Health Center, Sungai Penuh City, Jambi Province, the number of hypertension sufferers is 218 people in 2021. This researcher aims to determine the effect of counseling with poster media on the incidence of hypertension in elderly women. 55-64 years old in the working area of the Rawang Health Center full river city.This type of research uses Quasy Experimental which means pseudo-experiment while the design is One groups Pretest Posttest. The population of this study were all elderly women aged 55-64 years who were registered at the Rawang Public Health Center, namely 218 people. Realizing these calculations, the sample size was 68 elderly women 55-64 years old.The results of this study indicate that the average knowledge of the elderly with hypertension before counseling with hypertension poster media in the intervention group was 66.94 + 8,249 and in the control group was 65.20 + 13,490. The average knowledge of the elderly with hypertension after counseling with hypertension poster media in the intervention group was 71.00 + 9.908 and in the comparison group was 70.61 + 9.493. the average attitude of the elderly with hypertension before health education with poster media in the intervention group was 61.64 + 13.08, and in the control group was 61.44 + 12.83. the average attitude of the elderly with hypertension after health education with poster media increased in the intervention group 65.50 + 16.45 and in the control group 64.70 + 15.76.the effect of health education with poster media on hypertension management knowledge in elderly women aged 55-64 years in the intervention group and no effect of health education with poster media in the control group in the working area of the Rawang Public Health Center in Sungai Penuh City, Jambi Province.